Factors associated with job stress among employees in food service department at selected private hospitals in Malaysia - Ghazali, Hazrina; Mohd Amin, Rozaidah (Human Resource Management Academic Research Society, 2022)
The institutional food services industry is one of the most important sectors in Malaysia. In conjunction with institutional food services industry roles that provide services either in the government or public institutional operations, this industry has rapidly expanded in the coming years. Hence, the numbers of employees requested in this industry are getting high in demand in supplying services throughout the institutional operations. Despite the high demand in this industry, the exposure of job stress to the employee can cause turnover. Therefore, the purpose of this study is to examine the factors that contribute towards to job stress among food service employees at the private hospitals and identify the most influential factor that associated with the stress. This study also designed to examine the relationship between demographic characteristics of employees and job stress. The factors that used to conduct this study are workload, salary and working environment. This study used a quantitative approach through a self-administered survey questionnaire. 180 sets of questionnaires distributed to employees who were currently working in food service department at private hospitals. There were only 126 questionnaires returned and valid for further analysis. Data obtained were analyzed by using Statistic Packages for Social Science (SPSS) latest version. Based on the analysis, workload is the most influential factor of job stress and followed by the working environment as a second influential factor. Meanwhile, the salary factor did not significantly influence job stress among employees in this industry. Findings of study hopes will help the managers or owners in the institutional food service industry particularly the private hospitals to highlight these factors that lead to employee job stress. Additionally, the importance of this study is to encourage managers in focusing on these three factors in order to implement strategies to minimize stress at workplace.